Alasdair Scott Sutherland: The Spaghetti Tree. Mario and Franco and the Trattoria Revolution - Jaine, Tom (Petits Propos Culinaires, 2012)
Alasdair Scott Sutherland: The Spaghetti Tree. Mario and Franco and the Trattoria Revolution: Primavera Books, 2009, 255 pp., paperback, £14.99.